Surface-state-mediated electron transfer at nanostructured ZnO multipod/electrolyte interfaces - Parthasarathy, Meera; Ramgir, Niranjan S.; Sathe, Bhaskar R.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K. (Journal of Physical Chemistry C, 2007)
Redox kinetics of cyanoferrate(III) species adsorbed at an n-type ZnO multipod/electrolyte interface is explored using electrochemical techniques like cyclic voltammetry and impedance spectroscopy. The electrochemical impedance results are analyzed using a fluctuating energy level model, assuming isoenergetic tunneling of majority carriers through the Helmholtz layer. A shift in the slope of Mott-Schottky plots (C-sc(-2) versus E) together with evidence from cyclic voltammetry shows that the electron-transfer process is mediated by surface states formed because of the adsorption of ferricyanide ions (as evident from the results of Fourier transform infrared spectroscopy). More significantly, the pH of zero charge (point of zero zeta potential, pzzp) of ZnO multipods is found to be 4.5 (from capacitance vs pH plots) compared to that of bulk ZnO (pH 9.5), which could be explained on the basis of a lowering in the work function of the nanostructured semiconductor and its consequent susceptibility to the formation of surface states. This is in excellent agreement with our earlier observation of ultralow threshold field emission with this material in the light of the linear dependence of pzzp with work function of the electrode material. The flat-band potential of the nanostructures is found to be 200 mV more negative than that reported for bulk n-type ZnO electrodes, indicating a higher doping density in the former. A three-dimensional mapping of charge distribution in the surface states is attempted by correlating the capacitance response of the system subjected to a sinusoidal potential modulation to the semiconductor electrode with that resulting from a systematic variation of the redox potential of the dissolved acceptor (achieved by varying the pH of the electrolyte) which further reveals the polyenergetic nature of the surface states.

Selective cis-dihydroxylation of olefins using recyclable homogeneous molybdenum acetylide catalyst - Biradar, Ankush V.; Sathe, Bhaskar R.; Shubhangi B. Umbarkar; Dongare, Mohan K. (Journal of Molecular Catalysis A-Chemical, 2008)
Selective cis-dihydroxylation of various olefins has been carried out using molybdenum acetylide complex CpMO(CO)(3)(C CPh) (1) as catalyst and hydrogen peroxide as an efficient and environmentally benign oxidant. In case of cyclohexene, very high conversion (95%) and selectivity (86%) for cis-dihydroxylated product has been achieved using H2O2 as an oxidant and t-butanol as a solvent. cis-Dihydroxylation of other substrates like styrene, a-methyl styrene, limonene and cyclopentene has also been carried out with very high selectivity for diol. The catalyst and intermediate species have been characterized using FT-IR, UV-vis spectral analysis and XPS studies as well as cyclic voltametric studies. These studies suggest that molybdenum oxo-peroxo complex is the catalytically active species. The intermediate blue complex when characterized by ESI MS suggested the formation of dimeric molybdenum complex and XPS and cyclic voltametric studies confirm the presence of mixed valence Mo(V) and Mo(VI) in the reaction intermediate. Based on the characterization results possible mechanism for dihydroxylation is proposed. Interestingly, even though the catalyst is homogeneous; it could be recovered quantitatively by extraction in aqueous phase and recycled five times without any appreciable loss in cyclohexene conversion and selectivity for cis-1,2-cyclohexanediol. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: acetylide complex; cis-dihydroxylation; Homogeneous catalysis; Hydrogen peroxide; recyclable

Synthesis of Sb-doped SnO2 nanowires and hyperbranched structures - Sathe, Bhaskar R.; Patil, Mrudula; Walke, Pravin S.; Vivek, J. P.; Lele, Ashish K.; Pillai, Vijayamohanan K.; Mulla, Imtiaz S. (Science of Advanced Materials, 2009)
Branched nanostructures of semiconducting materials are of great interest for their potential applications in optoelectronic, photonic devices and sensors. We herein describe a facile single-step chemical vapor deposition route for the synthesis of Sb-SnO2 hyperbranched nanostructures comprised of elongated nanowires with 30-40 nm diameter and 10-20 Am length. The morphology and structure has been characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), selective area electron diffraction (SAED), and powder X-ray diffraction (XRD). Also, a possible mechanism is proposed for the growth of nanowires into the hyperbranched form on the basis of the substrate effect, the role of Au nanoparticles, and the effect of Sb doping on specific morphology evolution. Interestingly, electrical conductivity measurements as a function of temperature suggest a semiconducting behavior, despite being governed by different electron-transport mechanisms with activation energies of 0.55 and 0.17 eV, which correspond to pure SnO2 and Sb-SnO2 nanowires, respectively. A precise control over the operating parameters not only envisages custom-designed, branched structures by a simple and economical route but also offers an alternative method to the expensive and tedious nanofabrication techniques for industrial applications.
Keywords: Au Nanoparticles; chemical vapor deposition; Sb-SnO2 Hyperbranched Nanostructures

Synthesis of Rh-carbon nanotube based heterostructures and their enhanced field emission characteristics - Sathe, Bhaskar R.; Kakade, Bhalchandra A.; Kushwaha, Ajay; Aslam, Mohammed; Pillai, Vijayamohanan K. (Chemical Communications, 2010)
Selective decoration of Rh nanospheres on acid functionalized carbon nanotubes has been demonstrated using Al as a sacrificial substrate. Remarkable field emission has been observed for this heterostructure as a high current density of 170 mu A cm(-2) is generated at an ultra-low threshold of 300 V mu m(-1), compared to much smaller values for Rh nanospheres and carbon nanotubes separately.

Significant enhancement of formic acid oxidation using rhodium nanostructures - Balan, Beena K.; Sathe, Bhaskar R. (Journal of Nanoscience and Nanotechnology, 2012)
The electrocatalytic activity of as-synthesized shape selective Rh nanostructures has been demonstrated using cyclic voltammetry, revealing unique shape-dependant performance towards HCOOH oxidation. interestingly, the enhancement factor (R) for different shapes of Rh with respect to that of commercial Rh towards formic acid oxidation ranges up to 20,000% for cubes as compared to 17,500% for pyramids and 11,000% for hexagons respectively. Mechanistic pathway for comparatively better sensitivity of cubes as compared to other shapes has been correlated with the results of X-ray diffraction.
Keywords: electrocatalysis; Formic Acid Oxidation; Preferential Growth; Rhodium Nanostructures

Superior humidity sensor and photodetector of mesoporous ZnO nanosheets at room temperature - Gupta, Shobhnath P.; Pawbake, Amit S.; Sathe, Bhaskar R.; Late, Dattatray J.; Walke, Pravin S. (Sensors and Actuators B-Chemical, 2019)
Miniaturized sensor technology is vastly demanding multifunctional materials to fulfill many requirements simultaneously; instead of integrating various sensors into a single device. Efficient operation of these miniaturized sensors at room temperature is highly feasible and cost-effective. The humidity sensing and photodetection is precise merit of sensing in special usage like artificial skin. Sensitivity enhancement in both humidity and photodetection required the high surface area for adsorption as well as a high charge transfer mechanism. The two dimensional (2D) zinc oxide nanosheets (ZnO NS) is the ultimate structure for dimensionally confined transport properties owing to the specific surface atomic configuration that results in high sensitivity, low operating temperature, fast response and recovery, and improved selectivity. Furthermore, introducing porosity into 2D nanostructures has opened new opportunities to enhance the efficiency of sensors and detectors via increasing large surface area and tunable physical and chemical properties. Here we report preparation of mesoporous and highly crystalline 2D ZnO NS by a single step, template free, cost-effective chemical method. The structural and morphological characterizations of ZnO NS are carried out using XRD, FESEM, XPS, TEM respectively. The high-resolution TEM images emphasize sheet-like morphology with a thickness of around 18-22 nm. Further the mesoporous ZnO NS (MZNS) with the pore size between 5-10 nm are achieved by simple heat-treatment. XPS and PL study is confirming the oxygen deficiency in MZNS. The MZNS exhibits an excellent responsivity than PZNS with a fast response and rapid recovery time of 25 s and 5 s respectively along with good cyclic stability which is highly crucial for smart humidity sensor. Furthermore, it considerably enhances photo-sensor performance than pristine ZnO NS (PZNS) with (similar to)1 s response time as well as (similar to)1 s recovery time along with better stability. These promising results illustrate the great potential of MZNS for next-generation humidity sensors and photodetectors.
Keywords: humidity sensor; Mesoporous; nanosheets; Photo-detector